Performance of regional women's empowerment and child protection services in serving victims of sexual violence in North Sulawesi province - Reza Rinaldy Ordinary; Ella Wargadinata; Meltarini Meltarini (Jurnal Scientia, 2024)
This research was motivated by the less than optimal performance of the Regional Women's Empowerment and Child Protection Service at the Regional Technical Implementation Unit for Women and Child Protection (UPTD PPA) in serving victims of sexual violence in North Sulawesi province. This research aims to determine and analyze the performance carried out by the Regional Women's Empowerment and Child Protection Service at the Regional Technical Implementation Unit for Women and Child Protection (UPTD PPA). This research uses descriptive qualitative methods. The data sources used are primary data and secondary data. Data collection techniques through observation, interviews and documentation. Data analysis method using data reduction, data presentation and drawing conclusions. The results of this research indicate that the performance of the Regional Women's Empowerment and Child Protection Service at the Regional Technical Implementation Unit for Women and Child Protection (UPTD PPA) in serving victims of sexual violence in North Sulawesi province has not been fully implemented optimally, such as productivity is still less than optimal, resource support is good that human resources and financial resources as well as existing facilities and infrastructure are inadequate, then the Responsibility indicator has not yet provided the services that society needs as seen from the fulfillment of victims' rights through services from organizations that have not been obtained comprehensively, then the accountability indicator is also lacking. maximum according to the research results, the activities carried out by the agency have not reached the target, then the responsiveness indicator is quite good by building an online reporting application, and finally the service quality indicator is still not optimal, as can be seen from not all victims' rights being fulfilled comprehensively.